X‐ray diffraction imaging of fully packaged n–p–n transistors under accelerated ageing conditions. Issue 5 (30th August 2022) - Tanner, Brian K.; Danilewsky, Andreas; McNally, Patrick J.
Abstract : X‐ray diffraction imaging contrast from individual silicon n–p–n bipolar transistors within fully encapsulated packages under conditions of extremely high forward bias is interpreted as arising from the effects of current crowding in the emitter region. Abstract : X‐ray diffraction imaging was used to monitor the local strains that developed around individual n–p–n bipolar transistors within fully encapsulated packages under conditions of extremely high forward bias to simulate accelerated ageing. Die warpage associated with the packaging was observed to relax systematically as the polymer became viscous due to the temperature rise associated with the dissipation of heat in the transistor. The direct image size and intensity from the individual transistors were interpreted in terms of a model in which local thermal expansion is treated as a cylindrical inclusion of distorted material, contrast arising principally from lattice tilt. The extension of the thermal strain image along the emitter with increasing power dissipation was ascribed to the effect of current crowding in the emitter region. Weaker large‐area contrast associated with the base–collector region was interpreted as arising from the smaller change in effective misorientation at the high X‐ray energy of thermal lattice dilation in the base region.